Developing A Sustainable and Effective Capacity Major Logistic Hubs in Indonesia - Mohammad Annas; Humairoh (Asian Journal of Management, Entrepreneurship and Social Science, 2022)
The study observed goals to degree the effective capability of logistics companies in Indonesia. Capacity is measured by the average load factor served per period with the queuing theory approach. The data used in this study were obtained from observations covering weekdays and weekends where the logistics company operates. The records compiled to seize versions in demand on the primary, middle, and quit of the working day with the item of studies divided into three regions, particularly western, crucial, and eastern Indonesia. The common load element information and the common ready time inside the queue are then used to degree the not unusual shipping of logistics merchandise served. The results showed that an effective logistics hub in the central part of Indonesia and other regions was less efficient due to the lack of routing development as well as demographic and geographical problems. The study concludes that logistics routes in Indonesia are categorized by region and hubs. Currently, not all operators implement e-routing due to the backbone of the technology infrastructure as well as financial reasons. There are significant differences regarding the area or scope of work logistics and distribution channels, the number of arrival units, the time spent in the waiting room when unloading goods, as well as the level of effective capacity in distribution infrastructure in Indonesia.